Pengembangan dan identifikasi properti psikometris kuesioner intensi prososial berbasis skenario untuk anak dan remaja - Sutarimah Ampuni; Sukmo Bayu Suryo Buwono (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
This research aimed to construct and examine the psychometric properties of the Scenario-Based Prosocial Intention Questionnaire (SBPIQ), a scenario-based questionnaire to tap prosocial intentions in children and adolescents. We examined the 40 items of SBPIQ representing four dimensions of prosocial behaviors (helping, sharing, comforting, and cooperating). The items were proportionally attached to 10 scenarios of prosocial behaviors commonly found in children and adolescents daily life. Data collection involved 2615 participants who were females (56,67%) and males (43,33%), aged 7-18 YO (7-9 YO, 16,21%; 10-12 YO, 19,81%; 13-15 YO, 35,07%; 16-18 YO, 28,91%), and resided in rural (41,03%) and urban (58,97%) areas. Psychometric properties were identified from construct validity (through Exploratory Factor Analysis & Confirmatory Factor Analysis) and internal consistency (through Stratified Alpha testing). Results showed that the final version of SBPIQ with 24 items exhibited acceptable construct validity and reliability. Furthermore, factor analyses confirmed the multidimentionality of prosocial behavior. Four distinct factors were found to form the construct of prosocial behaviors, and one second-order factor was also found to bind these 4 factors. Other findings and important notes are discussed within this article.